Regulatory Transgression? Drivers, Aims and Effects of Money Laundering and Terrorism Financing Regulation in Pakistan - Sanaa, Ahmed (2020)
The harmonization of money laundering and terrorism financing regulation is a key feature of the contemporary global economy. Since 9/11 particularly, the remarkable growth of this field of regulation has been characterized by both scale and intensity. However, this drive towards regulatory convergence is puzzling: the efficacy of the regulation remains unproven while the content of the regulation poses significant challenges to both criminal justice systems and human rights frameworks. The corollary to these observations: who does the regulation benefit? With the understanding that all regulation is an expression of some interest/s, this study analyses the trajectory of this global regulation and its products. My aim is to understand who gains what from regulation and how they influence this regulatory evolution. Focusing on Pakistan, my research will examine how anti money laundering (AML) and counter terrorism financing (CTF) regulation and its increasing demands for information affects established power hierarchies in states, between states and among states. At the international and transnational levels, I’m interested in how a universal financial regulation discourse threatens basic rights and freedoms and how this exercise of power affects civil, political and economic rights in a country, its foreign policy as well as geopolitics. At the national level, I’m curious about how such regulatory power with its distinctive objectives interacts or conflicts with or even amplifies the control of established power centres in a polity. The analysis of power relations in the case of Pakistan will be particularly instructive for several reasons. First, the size of its formal economy is rivalled (if not surpassed) by the informal or black economy and the money laundering industry is all the more powerful for processing illicit funds from crime; corruption; and tradeand taxation-related malpractices. Second, Pakistan’s military establishment has long supported militancy as a foreign policy tool, both materially and financially, and to date orients its foreign policy accordingly. Finally, the military establishment also relies on intrusive surveillance tools to control civil society. The opacity of the discourse regarding international financial governance makes a closer scrutiny of its aims a critical imperative. By exploring the links between regulation, power, knowledge and surveillance, I hope to understand the aims of this power and offer a critique of financial regulation as a technique of power and the politics of making and administering AML/ CTF regulation, both across the globe and within states